2021
DOI: 10.1152/ajpheart.00810.2020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of menstrual cycle and menopause on internal carotid artery shear-mediated dilation in women

Abstract: This study aimed to elucidate the effects of change in estrogen during the menstrual cycle and menopause on shear-mediated dilation of the internal carotid artery (ICA), a potential index of cerebrovascular endothelial function. Shear-mediated dilation of the ICA and serum estradiol were measured in 11 premenopausal (Pre-M, 21±1yrs), 13 perimenopausal (Peri-M, 49±2yrs), and 10 postmenopausal (Post-M, 65±7yrs) women. Measurements were made twice within the Pre-M group at their early follicular (EF, lower estrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 62 publications
0
24
5
Order By: Relevance
“…Last, we do not consider how sex differences may influence ICA hemodynamics in children or adults. There is evidence that ICA dilation increases from the low to the high estradiol phase of the menstrual cycle (Iwamoto et al, 2021 ) and assessment of monthly hormonal changes, although challenging, would be valuable for a more thorough developmental understanding of CBF regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Last, we do not consider how sex differences may influence ICA hemodynamics in children or adults. There is evidence that ICA dilation increases from the low to the high estradiol phase of the menstrual cycle (Iwamoto et al, 2021 ) and assessment of monthly hormonal changes, although challenging, would be valuable for a more thorough developmental understanding of CBF regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study reported that the carotid artery dilation was improved with higher serum estradiol levels, even after controlling for age. These results point to an intrinsic role of estrogen in the regulation of CVD risk, independent of aging, through the menopause transition ( 69 ). Additionally, investigations into subclinical markers of CVD progression indicative of vascular disturbance also suggest dysfunction emerges across the menopause transition.…”
Section: Cvd and Menopausementioning
confidence: 82%
“…Recent research by Iwamoto and colleagues ( 69 ) examining internal carotid artery shear-mediated dilation as an early predictor of CVD found that dilation was impaired in peri- and post-menopausal women, as compared to pre-menopausal women. Importantly, women included in this trial were not using any type of medication, although there was no exclusion of prior use of HT.…”
Section: Cvd and Menopausementioning
confidence: 99%
“…The results suggest that declines in cerebrovascular function with ageing may be partially mediated by reduced levels of circulating oestradiol (Iwamoto et al . 2021). Whether the transient CO 2 test is reflective of changes in cerebrovascular NO‐mediated EDD with ageing, exercise and across the menstrual cycle or menopausal transition requires further investigation.…”
Section: Establishing Csmd As Clinically Relevantmentioning
confidence: 99%